Accession of Tumor Heterogeneity by Multiplex Transcriptome Profiling of Single Circulating Tumor Cells - Gorges, Tobias M; Kuske, Andra; Röck, Katharina; Mauermann, Oliver; Müller, Volkmar; Peine, Sven; Verpoort, Karl; Novosadova, Vendula; Kubista, Mikael; Riethdorf, Sabine; Pantel, Klaus (Clinical chemistry, 2016)
BACKGROUND: Transcriptome analysis of circulating tumor cells (CTCs) holds great promise to unravel the biology of cancer cell dissemination and identify expressed genes and signaling pathways relevant to therapeutic interventions. METHODS: CTCs were enriched based on their EpCAM expression (CellSearch(®)) or by size and deformability (Parsortix(TM)), identified by EpCAM and/or pan-keratin-specific antibodies, and isolated for single cell multiplex RNA profiling. RESULTS: Distinct breast and prostate CTC expression signatures could be discriminated from RNA profiles of leukocytes. Some CTCs positive for epithelial transcripts (EpCAM and KRT19) also coexpressed leukocyte/mesenchymal associated markers (PTPRC and VIM). Additional subsets of CTCs within individual patients were characterized by divergent expression of genes involved in epithelial-mesenchymal transition (e.g., CDH2, MMPs, VIM, or ZEB1 and 2), DNA repair (RAD51), resistance to cancer therapy (e.g., AR, AR-V7, ERBB2, EGFR), cancer stemness (e.g., CD24 and CD44), activated signaling pathways involved in tumor progression (e.g., PIK3CA and MTOR) or cross talks between tumors and immune cells (e.g., CCL4, CXCL2, CXCL9, IL15, IL1B, or IL8). CONCLUSIONS: Multimarker RNA profiling of single CTCs reveals distinct CTC subsets and provides important insights into gene regulatory networks relevant for cancer progression and therapy.
Keywords: Epithelial-Mesenchymal Transition; RNA, Neoplasm; RNA nádorová; transkriptom; lidé; epitelo-mezenchymální tranzice; nádorové cirkulující buňky; Transcriptome; Tumor Cells, Cultured; Neoplastic Cells, Circulating; Gene Expression Profiling; nádorové buňky kultivované; stanovení celkové genové exprese; Humans